Trends in incidence, survival and mortality of childhood and adolescent cancer in Austria, 1994–2011. (June 2016) - Karim-Kos, Henrike E.; Hackl, Monika; Mann, Georg; Urban, Christian; Woehrer, Adelheid; Slavc, Irene; Ladenstein, Ruth
Highlights: Since the 1980s high enrolment in clinical studies (>90%) and centralization of care. Cancer incidence in adolescents increased to a stronger extent than in children. Five-year survival improved by 5–7% reaching 86% resulting in declining mortality. Neuroblastoma screening (1991–2003) affected trends of neuroblastoma. Low incidence of retinoblastoma in the past due to referring pattern to Germany. Abstract: Background: This is the first study on trends in cancer incidence, survival and mortality for children and adolescents in Austria. The aim was to assess to what extent progress against childhood and adolescent cancer has been made in Austria since the 1990s and to complement the childhood and adolescent cancer trends for Central Europe. Methods: All malignant neoplasms and non-malignant tumours of the Central Nervous System (CNS) in patients aged less than 20 years and diagnosed between 1994 and 2011 (N = 5425) were derived from the Austrian National Cancer Registry (ANCR). Incidence and mortality trends were evaluated by the average annual percentage change (AAPC). Observed survival rates were calculated based on follow-up until December 31st 2013. Results: Childhood cancer remained stable with 182 cases per million in 2011, but rose among girls by 1.4% (95% CI: .1, 3.6) annually due to an increase of non-malignant CNS tumours and Non-Hodgkin lymphoma. Adolescent cancer rose by 1.5% (95% CI: .4, 2.6) annually, from 182 cases per million in 1994–269 in 2011, especially leukaemia, CNS tumours (including non-malignant types) and epithelial tumours. Five-year survival improved by 5–7% reaching 86% for both groups ( p  < .05). Mortality declined by −2.4% (95% CI: −3.7, −1.2) and −2.0% (95% CI: −4.6, .5), respectively, especially for childhood leukaemia. Conclusion: Progress is demonstrated by improved survival and declined mortality most likely related to improved diagnostic techniques, more effective therapeutic regimes, supportive care and a central advisory function of experts in the Austrian paediatric oncology.